Growth of delafossite CuAlO2 single crystals in a reactive crucible. (18th January 2023) - Kim, Du Hyung; Kong, Minsik; Kang, Myeongjun; Kim, Minjae; Kim, Seohee; Kim, Youngwook; Yoon, Sangmoon; Ok, Jong Mok
Abstract: Delafossite oxide CuAlO2 has received great attention as a promising p-type conducting oxide. In this work, high-quality CuAlO2 single crystals with a size of several millimeters (mm) are successfully synthesized with a reactive crucible melting method. The crystals are characterized by x-ray diffraction, scanning electron microscopy with energy-dispersive spectroscopy, transport measurement, and magnetic susceptibility measurement. The CuAlO2 single crystals show semiconducting behavior with hole carriers, which is consistent with other crystals grown by the conventional slow-cooling method. This growth method we reported here eliminates the process of removing the remaining flux, allowing easy access to the high-quality single crystals. This new approach to growing high-quality delafossite oxide CuAlO2 with a few mm size is important for new technologies that demand p-type semiconductor-based device fabrication.